Menggali Kearifan Lokal untuk Pembangunan Ekonomi Berkelanjutan: Studi Kasus Bali - Ni Made Suarminiati; Nyoman Subanda (Universitas Medan Area, 2025)
By 2045, Indonesia aims to become the world's fourth-largest economy, with a projected value of USD 8.89 trillion. Achieving this target requires integrating local wisdom into economic strategies, reflecting the nation’s cultural heritage and sustainability goals. This study examines the gap between these national aspirations and ground realities, focusing on the role of local wisdom in supporting sustainable economic growth. Using a literature review, secondary data, and interviews with key informants, the study explores “Tri Hita Karana” as a basis for economic development. The findings show that although government policies, such as the regional action plan and green economy initiatives, align with local traditions, their implementation still faces challenges such as regulatory inconsistencies, weak coordination, limited access to capital, and a lack of human resources. The study also emphasizes the importance of aligning national strategies with local potential, particularly in regions like Bali, where the creative economy is closely linked to cultural heritage. Unlike previous studies, this research provides a comprehensive analysis of how local wisdom can bridge the gap between policy ambitions and on-the-ground realities, offering practical recommendations to strengthen MSMEs, attract investment, and support the green economy. This approach enhances the competitiveness of local economies while preserving cultural identity.